ASEAN As a Security Community: Challenges of Conceptualization - I. A. Nikiforov (Вестник Московского Университета. Серия XXV: Международные отношения и мировая политика, 2020)
ASEAN Political-Security Community (APSC) is the ASEAN’s newest and ambitious initiative aimed at maintaining peace in the region by establishing common norms and standards of good conduct. The launch of the APSC has provoked an intense debate among experts on ASEAN on whether the Association could be regarded as a security community in the classic theoretical sense. The author examines arguments in the key participants of this debate and presents its own point of view. The paper shows that constructivist scholars led by A. Acharya argue that their interpretation of the classic security community concept is relevant to the situation in the Southeast Asia, which is characterized by a strong sense of regional identity and a constitutive political role of norms. Their opponents represented by realist scholars, such as N. Khoo and M. Leifer, demonstrate the irrelevance of constructivist ideas to the ASEAN realities and emphasize the inability of Southeast Asian states to build a functioning security community. The conclusion is drawn that while both approaches have their own drawbacks, it would be premature to choose one or the other because the establishment of the security community in the ASEAN is an ongoing process, which is still far from complete. Therefore, the most promising and relevant for current political situation in the region is a moderately critical approach that treats ASEAN as a security regime rather than a security community.